Philippine export directory, 1997. (Makati City Pacific Trade Media Publications, 1997)
This is a compilation of a number of featured articles (on the Philippine economy; industrial goods/services; garments; shoes, bags, jewelries; food/beverages; furniture/houseware; and human resources); information on government and trade associations including foreign embassies, the Philippine consulate, trade and industry associations; a supplier's profile section; buyer's guide (bags, shoes, fashion, accessories, industrial, electrical, automotive construction, food/beverages, pharmaceutical, cosmetics, garments fabrics, handicrafts, furniture home accessories); and services ranging from airlines, banks, communication, export financing, freight forwarders and cargo, hotels, service exports, shipping lines, and travel tours.
Cover title.
Keywords: Exports -- Philippines -- Directories; Foreign trade promotion -- Philippines -- Directories